ACCUMULATION OF CADMIUM AND LEAD IN COMMERCIALLY IMPORTANT FISH SPECIES IN THE GULF OF GEMLİK, MARMARA SEA, TURKEY - (:unkn) unknown (My University, 2017)
0

The aim of this study was to investigate the concentrations of cadmium (Cd) and lead (Pb) in gill and muscle tissues of ten commercial fish caught from the Gulf of Gemlik, Marmara Sea, Turkey. Ten commercially important marine fish species were obtained monthly from the local fishermen. The Cd and Pb levels in muscle and gill tissues of the fish samples were evaluated using atomic absorption spectrophotometer (Shimadzu 6701, Shimadzu, Tokyo, Japan). In July 2011, the highest concentrations of Cd were found in the gill tissue of Sardinella maderensis, Solea vulgaris and Belone belone (3.62, 3.46 and 3.05µg g-1, respectively). In March 2011, the highest concentrations of lead were observed in the gill tissues of S. vulgaris and B. Belone (9.48 and 6.74 µg g-1, respectively), and the muscle tissue of S. maderensis (7.07 µg g-1). Generally, the levels of Cd and Pb were found very high for the than the tolerance limits of Turkish Food Codex, European Union (EU) and the World Health Organization (WHO) standards
Keywords: Deniz ve Tatlı Su Biyolojisi